Greater volumes are required to reduce muscle performance in well-trained individuals - Dinato de Lima, F.; Vieira, A.; Matias Correia, A. L.; Moreno Lima, R.; Correa da Fonseca, A.; Bottaro, M. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
A specific drop jumps (DJs) protocol (using 100 jumps) has been largely used to induce muscle damage. However, it failed to show relevant drop in performance in well-trained individuals. Trained subjects may require a protocol with greater volume to induce decrease of muscle performance. The aim of this study was to assess muscle performance after two DJs damaging protocols with different volumes in well-trained individuals. Eighteen strength and/or power-trained males (4.92 ± 2.78 years of training experience) were randomly assigned into one of two groups: DJ100 (five sets of 20 DJs) or DJ140 (seven sets of 20 DJs), with 2-min of rest interval. DJs were performed from a 60-cm box. After landing, the volunteers performed a maximal vertical rebound jump. Muscle swelling increased significantly on both DJ100 and DJ140 (p < 0.001). Maximal isometric torque (MIT) decreased significantly on both DJ100 (p = 0.005) and DJ140 (p < 0.001). MIT showed no between-group difference on pre-assessment (p = 0.815). However, on post-assessment, MIT was significantly lower on DJ140 than DJ100 (p = 0.043). Countermovement jump (CMJ) decreased significantly on DJ140 (p = 0.001), but not on DJ100 (p = 0.802). There was no between-group difference on pre-assessment (p = 0.978). However, on post-assessment, CMJ was significantly lower on DJ140 than DJ100 (p = 0.038). DJ140 induced greater drop in isometric strength than DJ100 and only DJ140 significantly reduced jump performance. These results demonstrated that well-trained individuals require a great volume of DJs to reduce substantially muscle performance.